1994
DOI: 10.1017/s0950268800057575
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mixed foot–and–mouth disease virus infections in Saudi Arabia: prolonged circulation of an exotic serotype

Abstract: Plaque purification of foot-and-mouth disease (FMD) type O viruses isolated from cattle in Saudi Arabia showed the presence of mixed serotype infections. Sixteen out of 31 samples collected between 1985 and 1991 also contained Asia 1 virus, a serotype which had previously only been isolated from a single outbreak in that country in 1980. Nucleotide sequences of the Asia 1 component of all these samples revealed little variation and showed that they were closely related to both a Russian lapinized vaccine virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 16 publications
2
27
0
Order By: Relevance
“…Virus extinction was not reported, and the two serotypes were shown to cycle equally through time. Interestingly, mixed infection with type O and Asia 1 in cattle has been described, with both viruses coexisting for an extended period of time (8). Therefore, coinfections with different FMDV serotypes may have distinct consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus extinction was not reported, and the two serotypes were shown to cycle equally through time. Interestingly, mixed infection with type O and Asia 1 in cattle has been described, with both viruses coexisting for an extended period of time (8). Therefore, coinfections with different FMDV serotypes may have distinct consequences.…”
Section: Discussionmentioning
confidence: 99%
“…However, SAT-1 is the serotype most frequently isolated from buffaloes (Nick Knowles, personal communication). Isolates of different SAT serotypes are known to exist as mixed infections, with isolates of all three serotypes being detected on occasion from buffalo esophageal-pharyngeal fluid (OPF); similarly, there are field examples of mixed infections of type O and Asia-1 viruses in cattle (7,8). It is unclear why certain FMDV serotypes exist in discrete geographical regions, while other serotypes, for example, type O, have a more global distribution (9).…”
mentioning
confidence: 99%
“…The field samples in mPCR, produced a single band of Asia1 serotype of FMDV. Woodbury et al (1994) analyzed field specimen (Sau 8/88) from Saudi Arabia and reported that O serotype was dominant followed by Asia 1 to some extent. The results were different from present study due to varied geographical distribution of different serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of dual infections in the field involving strains of FMD virus serotype Asia I alongside strains of serotype 0 in Saudi Arabia has been recently reported [97]. Studies showed that the viruses persisted together in a stable manner within the country for several years, and that although the 0 serotype was always dominant, Asia I was never completely eliminated.…”
Section: Persistent Mixed Infectionsmentioning
confidence: 98%